Hadith #79 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
He will not enter Paradise whose neighbour is not secure from his wrongful conduct.
Grade: Sahih

Hadith #264 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
I heard the Messenger of Allah observing: He who took an oath on the property of a Muslim without legitimate right would meet Allah and He would be angry, with him. Then the Messenger of Allah (ﷺ) in support of his contention recited the verse:” Verily those who barter Allah’s covenant and their oaths at a small price.
Grade: Sahih

Hadith #368 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
Verily the Messenger of Allah said: The last to enter Paradise would be a man who would walk once and stumble once and be burnt by the Fire once. Then when he gets beyond it, he will turn to it and say: Blessed is He Who has saved me from thee. Allah has given me something He has not given to any one of those in earlier or later times. Then a tree would be raised up for him and he will say: O my Lord I bring me near this tree so that I may take shelter in its shade and drink of its water. Allah,
Grade: Sahih

Hadith #803 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
The Messenger of Allah (ﷺ) taught me tashahhud taking my hand within his palms, in the same way as he taught me a Sura of the Qur’an, and he narrated it as narrated above.
Grade: Sahih

Hadith #1735 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
Wretched is the man who says: I forgot such and such a sura, or I forget such and such a verse, but he has been made to forget.
Grade: Sahih

Hadith #2425 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
The dawn is not like it, as one says (and he lifted his hand) till he (dispersed his fingers) and said: It is like this.
Grade: Sahih

Hadith #3546 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
Do you know ‘Abdullah b. Umar? He said: Yes. He said: It was he who divorced his wife jn the state of menses and ‘Umar went to Allah’s Apostle (ﷺ) and gave him this information. and he commanded him that he should take her back; and he (Abu Tawus) said: I did not hear any addition to this (hadith) from my father.
Grade: Sahih

Hadith #4518 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
While the Messenger of Allah (ﷺ) was saying his prayer near the Ka’ba and Abu Jahl with his companions was sitting (near by), Abu Jahl said, referring to the she-camel that had been slaughtered the previous day: Who will rise to fetch the foetus of the she-camel of so and so, and place it between the shoulders of Muhammad when he goes down in prostration (a posture in prayer). The one most accursed among the people got up, brought the foetus and, when the Prophet (ﷺ) went down in prostrati
Grade: Sahih

Hadith #5520 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
The Messenger of Allah (ﷺ) said to me: The sign that you have been permitted to come in is that the curtain is raised or that you hear me speaking quietly until I forbid you.
Grade: Sahih

Hadith #6608 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
0 Allah, enable me to derive benefit from my husband, Allah’s Messenger (ﷺ), and from my father Abu Sufyan, and from my brother Mu’awiya. Allah’s Messenger (ﷺ) said to her: Verily, you have asked Allah about the durations of life already set, and the steps which you would take, and the sustenances the share of which is fixed. Nothing would take place earlier than its due time, and nothing would be deferred beyond that when it is due. So, if you were to ask Allah about your safety from
Grade: Sahih

Hadith #6855 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
Do you think that Allah hears as we speak? The other one said: He does hear when we speak loudly and He does not hear when we speak in undertones, and still the other one said: If He listens when we speak loudly, He also listens when we speak in undertones. It was on this occasion that this verse was revealed:” You did not conceal yourselves lest your ears, your eyes and your skins would stand witness against you” (xli. 22).
Grade: Sahih

Hadith #7356 - Sahih Muslim - ibn Mas'ud (Sahih Muslim)
Since our acceptance of Islam and the revelation of this verse in which Allah has shown annoyance to us:” Has not the time yet come for the believers that their hearts should be humble for the remembrance of Allah?” (lvii. 16), there was a gap of four years.
Grade: Sahih